Usage of Nivolumab - Platinum Containing STAT1 Molecule for Suppression PD-1/PD-L1 Genes in PD-1/PD-L1 Expressing Cancer Cells (Global Journal of Medical Research, 2022)
Blockage of PD-1 proteins by immune checkpoint inhibitors showed an accepted therapeutic effect in cancer. But; tumor microenvironment exerts its antitumor influence by various mechanisms. Malignant cells have the ability of PD-1/PD-L1 protein over synthesis, which can be a defense action against immune checkpoint inhibitors and immunotherapy. Binding nivolumab with platinum-containing STAT1 will be used to reduce PD-1 genetic level. Nivolumab has the option of endocytosis, while STAT1 is the transcription factor that binds to the DNA, specifically PD-1 gene. STAT1 is the activated protein in response to multiple cytokines stimulation of cancer cells, which are the same for increasing PD-1/ PD-L1 upregulation. The used STAT1 in our therapeutic strategy is the activated form and loaded with platinum particles for damaging DNA bases in PD-1 promoter regions upon translocation to the nucleus. STAT1platinum molecule is connected to nivolumab Fc region by solamargine polymer for selective cancer cell targeting.
Keywords: A5 complex; IFN-3B3; endocytosis; cytokines; solamargine; phosphorylation